2017
DOI: 10.17235/reed.2017.4795/2016
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically placed stents: a useful alternative for the management of refractory benign cervical esophageal stenosis

Abstract: Introduction: Benign esophageal strictures are relatively frequent and can severely affect the quality of life of a patient. Stenting has been proposed for the treatment of refractory cases. Lesions affecting the cervical esophagus are more difficult to treat, and the placement of stents in this location has traditionally been restricted due to potential adverse events. The aim of this study was to describe the efficacy and safety of endoscopic stenting in the management of refractory benign cervical esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…It is believed that the typical wide flanges and short lengths of LAMSs may prevent stent migration. To date, LAMSs have only been investigated in mixed study populations restricted by small sample sizes [90][91][92][93][94]. More studies are needed to evaluate their potential benefit in RBES patients.…”
Section: Recommendationmentioning
confidence: 99%
“…It is believed that the typical wide flanges and short lengths of LAMSs may prevent stent migration. To date, LAMSs have only been investigated in mixed study populations restricted by small sample sizes [90][91][92][93][94]. More studies are needed to evaluate their potential benefit in RBES patients.…”
Section: Recommendationmentioning
confidence: 99%
“…In addition, dysphagia recurrence has been described as a consequence of BDS treatment [38]. While late dysphagia occurrence is frequently related to treatment failure and recurrence of the RBES, early dysphagia might be the result of BDS collapse, or more frequently tissue in-/overgrowth [43,44]. This hyperplastic tissue may significantly obstruct the esophageal lumen, leading to dysphagia.…”
Section: Safety Outcomes -Complicationsmentioning
confidence: 99%
“…For BDS-associated hyperplasia different techniques have been reported. Among them, coagulation using argon plasma, endoscopic balloon dilations and placement of a sequential stent have been applied with variable results [43][44][45][46].…”
Section: Safety Outcomes -Complicationsmentioning
confidence: 99%
“…Stents made of polydioxanone can be used in a variety of hollow organs, such as the esophagus [ 25 , 26 , 27 , 28 , 29 ], intestine [ 30 ], trachea [ 31 , 32 , 33 , 34 , 35 ], and bile ducts [ 22 , 24 , 36 , 37 , 38 ]. Rejchrt et al reported that a PPDX stent placed in a gastrointestinal tract maintained its properties (radial force and integrity) for 6–8 weeks, and the stent disintegration occurred after 11–12 weeks.…”
Section: Introductionmentioning
confidence: 99%